Low-gloss pet matte film and process for making same
Patent Information
- Application Number
- CN202611132827.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-29
- Publication Date
- 2026-10-30
AI Technical Summary
然而,无机消光剂与PET基体的相容性较差,在加工过程中容易团聚,导致薄膜雾度不均匀、表面出现晶点或白点等外观缺陷;大量添加消光剂会破坏PET分子链的连续性和取向结构,使薄膜的力学性能显著下降,尤其是断裂伸长率和耐弯折性急剧降低,薄膜变脆,难以满足后续加工和使用对柔韧性的要求
本发明制备的PET哑光膜具有低光泽度、雾度适当,实现了优异的低光泽视觉效果,光扩散效果均匀柔和;薄膜表面粗糙度大,能够赋予其出色的表面附着力,油墨或涂层结合牢固,印刷复合性能优异,且韧性好、不易开裂,能够满足特定装饰材料、汽车装饰等高端领域对薄膜外观和耐用性的严苛要求,还可替代下游热熔性喷涂类产品。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention relates to the field of polymer materials technology, specifically to a low-gloss PET matte film and its preparation process. Background Technology
[0002] Biaxially oriented polyethylene terephthalate (PET) film possesses excellent mechanical properties, heat resistance, transparency, and dimensional stability, making it widely used in packaging, decoration, optoelectronic displays, and electronics. With rising consumer demand and changing aesthetic preferences, the demand for low-gloss, high-haze matte PET film is increasing in applications such as appliance finishes, automotive interiors, high-end packaging, and electronic product protective films. Its unique hazy texture and smooth feel, along with its ability to effectively conceal fingerprints and scratches, have made it a market favorite. Furthermore, in the automotive trim and specific decorative materials sectors, downstream companies traditionally use hot-melt spraying to achieve matte surface effects. However, this process suffers from long construction cycles, high VOC emissions, and high costs. The industry urgently needs an environmentally friendly matte film product that can be directly laminated as an alternative.
[0003] Currently, the common method for preparing matte PET films is to add inorganic matting agents (such as silica, calcium carbonate, talc, kaolin, etc.) or other types of particulate materials to PET resin, and then form a film through biaxial stretching after melt blending. However, inorganic matting agents have poor compatibility with the PET matrix and are prone to agglomeration during processing, resulting in uneven haze, crystal points, or white spots on the surface of the film. Adding large amounts of matting agents will disrupt the continuity and orientation structure of the PET molecular chains, significantly reducing the mechanical properties of the film, especially the elongation at break and bending resistance, making the film brittle and unable to meet the flexibility requirements of subsequent processing and use. Summary of the Invention
[0004] To facilitate a clearer understanding of the technical solutions and effects of this invention, the following detailed description, in conjunction with specific embodiments, is provided. Unless otherwise specified, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. In case of conflict, the definitions in this specification shall prevail.
[0005] Unless otherwise specified, "room temperature" in this invention refers to 25±2℃.
[0006] The first aspect of the present invention provides a low-gloss PET matte film, the PET matte film being made from raw materials comprising the following components: PET chips, functional masterbatch A and functional masterbatch B; the functional masterbatch A comprising a modifying agent, a thermoplastic polyester elastomer and an olefin copolymer containing epoxy functional groups; the functional masterbatch B comprising carboxylated cellulose nanofibers and PET resin; the modifying agent being a composite microparticle surface-treated with a silane coupling agent, the composite microparticle being composed of layered silicates and cross-linked silicone resin microspheres.
[0007] As a preferred technical solution of the present invention, the layered silicate is mica powder. The mica powder in the present invention can be any type of mica powder in the art. For example, the mesh size of the mica powder is 2000~5000 mesh. By mass fraction, the main components of the mica powder are: silicon oxide 44%-50%, aluminum oxide 20%-33%, potassium oxide 9%-11%, ferric oxide 2%-6%, sodium oxide 0.95%-1.8%, magnesium oxide 1.3%-2%, and the balance is other unavoidable conventional components.
[0008] The cross-linked silicone resin microspheres in this invention can be obtained commercially, for example, the cross-linked silicone resin microspheres are of the American MSE silicone microsphere type.
[0009] As a preferred embodiment of the present invention, the mass ratio of layered silicate to cross-linked organosilicon resin microspheres in the composite microparticles is (0.5~2):1, preferably (1~1.2):1.
[0010] As a preferred embodiment of the present invention, the silane coupling agent is γ-aminopropyltriethoxysilane (KH550).
[0011] The modified additives in the functional masterbatch A of this invention can reduce the gloss of PET matte film while increasing its roughness and haze. It is speculated that this is because the mica flakes in the modified additives are oriented along the film surface during biaxial stretching, which can strongly scatter light. The cross-linked silicone resin microspheres are elastic and not completely compatible with PET, which can form spherical protrusions on the surface, increasing diffuse reflection. The two work together to form a multi-scale rough structure, which causes light to be scattered multiple times on the surface, thereby reducing gloss, increasing haze and achieving a uniform diffusion effect.
[0012] As an example, the preparation method of the modified additive includes: weighing mica powder and cross-linked organosilicon resin microspheres and adding them to a mixer, setting the stirring speed to 300~800 rpm, and simultaneously turning on the heating jacket to raise the material temperature to 50~70℃, and stirring at this temperature for 10~30 min; then weighing KH550 coupling agent, the amount of which is 0.5%~1.5% of the total mass of mica powder and cross-linked organosilicon resin microspheres, preferably 0.6%~0.8%, and dissolving the KH550 coupling agent in 5 Dissolve the coupling agent completely in approximately 10 times its mass of anhydrous ethanol by stirring. Adjust the mixer speed to 1200-1800 rpm and lower the temperature to room temperature. Add the coupling agent solution to the mixer and continue stirring for 1-10 minutes. Discharge the mixture and transfer it to a vacuum oven. Dry the mixture at 70-80℃ and -0.09 MPa for 1-6 hours. After cooling to room temperature, pass the mixture through a 100-300 mesh sieve to obtain the modified additive.
[0013] As a preferred technical solution of the present invention, the thermoplastic polyester elastomer is TPEE (PBT-PTMG block copolymer) resin. Preferably, the melt flow rate of the TPEE resin at 230°C and 2.16 kg is 25~35 g / 10 min. The TPEE resin in the present invention can be obtained commercially, for example, the grade of TPEE resin is LONGLITE® TPEE 1155LL.
[0014] As a preferred embodiment of the present invention, the olefin copolymer containing epoxy functional groups is an ethylene-acrylate-glycidyl methacrylate terpolymer. Preferably, the melt flow rate of the ethylene-acrylate-glycidyl methacrylate terpolymer at 190°C and 2.15 kg is 4~8 g / 10 min. The ethylene-acrylate-glycidyl methacrylate terpolymer in the present invention can be obtained commercially, for example, the brand name Arkema Lotader AX8900.
[0015] As a preferred technical solution of the present invention, the weight ratio of the modified additive, thermoplastic polyester elastomer and epoxy functional group-containing olefin copolymer is (15~25):(35~45):(8~15), preferably (20~22):(38~42):(10~12).
[0016] The study found that the addition of modifying agents leads to a decrease in the flexibility of matte PET films. In this invention, the use of TPEE (polyether ester elastomer) in combination with an ethylene-acrylate-glycidyl methacrylate terpolymer not only increases the elongation at break of the matte PET film but also further reduces its gloss and increases its haze. This is presumably because TPEE dispersed in the continuous PET phase forms elastomer microregions, which can absorb impact energy, induce crazing and shear yielding, and significantly improve the elongation at break. Furthermore, the difference in refractive index between TPEE and PET generates additional light scattering, which can further reduce gloss and increase haze, resulting in a superior diffusion effect.
[0017] As a preferred technical solution of the present invention, the functional masterbatch A comprises, by weight: 15-25 parts of modifying agent, 35-45 parts of thermoplastic polyester elastomer, 8-15 parts of olefin copolymer containing epoxy functional groups, 0.1-0.5 parts of antioxidant, 0.1-0.5 parts of dispersant, and 20-30 parts of PET resin.
[0018] The antioxidants mentioned above can be any antioxidant in the art, including but not limited to at least one of antioxidant 1010, antioxidant 168, and antioxidant 626.
[0019] The dispersant described above can be any dispersant in the art, including but not limited to at least one of calcium stearate, zinc stearate, magnesium stearate, barium stearate, pentaerythritol stearate (PETS), glyceryl monostearate (GMS), butyl stearate, ethylene bis-stearamide (EBS), oleamide, and erucamide.
[0020] The aforementioned PET resin is commercially available, for example, the PET resin model is Skyrol® SL30U.
[0021] The functional masterbatch A in this invention can be obtained by melt blending the various components of functional masterbatch A. As an example, the preparation method of functional masterbatch A includes: adding 15-25 parts by weight of modifying agent, 35-45 parts by weight of TPEE resin, 8-15 parts by weight of olefin copolymer containing epoxy functional groups, 0.1-0.5 parts by weight of antioxidant, 0.1-0.5 parts by weight of dispersant, and 20-30 parts by weight of PET resin into a mixer; stirring at room temperature for 2-5 minutes at a speed of 300-500 rpm; and then... Stir at 1200-1800 rpm for 5-10 minutes to ensure thorough and uniform mixing of all components. Feed the mixture into a twin-screw extruder for melt extrusion. Set the extruder temperatures sequentially from the feed port to the die as follows: Zone 1 200-220℃, Zone 2 230-245℃, Zone 3 250-260℃, Zone 4 260-270℃, Zone 5 260-270℃, Zone 6 255-265℃, Zone 7 245-255℃, and the die temperature 235-245℃. Turn on the vacuum pump in the exhaust section to achieve a vacuum level below -0.08 MPa to remove small molecule volatiles. Control the screw speed at 100-150 rpm. The extruded strip from the die head is fully cooled in a water tank (water temperature 15~25℃), the surface moisture is dried by an air knife, and then it enters the pelletizer to be pelletized to obtain cylindrical functional masterbatch A with a diameter of 2~3mm and a length of 3~4mm.
[0022] As a preferred embodiment of the present invention, the carboxylated cellulose nanocrystals have a diameter of 2-15 nm and a length of 100-300 nm. The carboxylated cellulose nanocrystals of the present invention are commercially available, for example, purchased from Angxing New Carbon Materials Changzhou Co., Ltd.
[0023] As a preferred embodiment of the present invention, the mass ratio of carboxylated cellulose nanocrystals to PET resin in the functional masterbatch B is (10~20):100, preferably (12~18):100.
[0024] In this invention, the PET resin in functional masterbatch B can be the same as the PET resin in functional masterbatch A.
[0025] Further research revealed that the addition of TPEE (polyether ester elastomer) to the ethylene-acrylate-glycidyl methacrylate terpolymer caused stickiness on the surface of the matte PET film. This invention further addresses this issue using functional masterbatch B, presumably because carboxylated cellulose nanofibers possess high crystallinity and rigidity modulus. During the cooling and heat setting of the PET melt, they act as physical crosslinking points. Their nanoscale size and carboxyl groups can form hydrogen bonds with carboxyl groups in PET or react with epoxy groups to form a network structure. This network restricts the movement and migration of TPEE dispersed in the continuous PET phase to form elastomer microregions, thus suppressing surface stickiness. Furthermore, since carboxylated cellulose nanofibers are smaller than most visible light wavelengths and their refractive index is close to that of PET, the visible light scattering generated in the film is extremely weak, contributing very little to the overall haze and gloss of the film, and essentially not interfering with the matte effect dominated by the modifying additives. However, when the dosage is too high, the nanoparticles are prone to agglomeration, forming micron-sized aggregates. These aggregates will disrupt the uniformity of surface roughness, produce irregular large protrusions, cause the gloss to rebound and increase, and the haze to fluctuate abnormally. At the same time, too many rigid particles will antagonize the toughening effect of TPEE and ethylene-acrylate-glycidyl methacrylate terpolymer, leading to a decrease in elongation at break.
[0026] The functional masterbatch B in this invention can be obtained by melt blending its various components. As an example, the preparation method of functional masterbatch B includes: adding carboxylated cellulose nanocrystals and PET resin to a mixer at a mass ratio of (10~20):100, stirring at 500~800 rpm for 10~15 minutes to achieve initial homogeneity; feeding the mixture into a twin-screw extruder for melt extrusion. The temperatures of each zone of the extruder from the feed port to the die are set sequentially as follows: Zone 1 170~190℃, Zone 2 190~210℃, Zone 3 200~220℃, Zone 4 205~225℃, Zone 5 200~220℃, and the die temperature is 190~210℃. Due to the limited heat resistance of carboxylated cellulose nanocrystals, the temperature of each zone should not exceed 225℃ to prevent carbonization and discoloration. In the exhaust section, a vacuum pump can be turned on, and the vacuum level is controlled at -0.06~-0.08MPa to remove moisture and trace volatiles. The screw speed is controlled at 100~150rpm. The extruded strip from the die is fully cooled in a water tank (water temperature 20±5℃), the surface moisture is dried with an air knife, and then it enters the pelletizer to pelletize, obtaining cylindrical functional masterbatch B with a diameter of 2~3mm and a length of 3~4mm.
[0027] The PET chips in this invention refer to sheet materials made of polyethylene terephthalate, which can be any type of PET chip in the art capable of preparing films. This invention does not have any special limitation on their source. For example, FG600 type PET chips provided by Yizheng Chemical Fiber can be used.
[0028] As a preferred technical solution of the present invention, the mass ratio of the PET chips, functional masterbatch A and functional masterbatch B is (7~9):(1~2.5):(1~2), preferably 8:(1.3~1.8):(1~1.8).
[0029] The second aspect of the present invention provides a process for preparing the low-gloss PET matte film described in the first aspect of the present invention, comprising the following steps: mixing PET chips, functional masterbatch A and functional masterbatch B in a certain proportion and drying them until the moisture content is ≤50ppm; melting and extruding the dried mixture through a single screw extruder, casting it onto a cooling roller through a T-die to obtain a cast sheet; biaxially stretching the cast sheet, heat-setting it after stretching, cooling it, and winding it up to obtain the low-gloss PET matte film.
[0030] As a preferred technical solution of the present invention, the barrel temperature of the single screw extruder from the feed port to the die head is as follows: Zone 1 230~250℃, Zone 2 260~280℃, Zone 3 280~290℃, Zone 4 285~295℃, Zone 5 280~290℃, and the die head temperature is 270~280℃; the surface temperature of the cooling roller is 25~35℃.
[0031] As a preferred technical solution of the present invention, the biaxial stretching adopts a step-by-step stretching method of first longitudinal and then transverse. The longitudinal stretching temperature is 80~90℃ and the stretching ratio is 3.2~3.6 times; the transverse stretching temperature is 110~130℃ and the stretching ratio is 3.5~4 times.
[0032] As a preferred technical solution of the present invention, the heat setting temperature is 220~240℃ and the time is 15~30 seconds; after heat setting, it is cooled to below 40℃ through a slow cooling zone and a fast cooling zone; the inlet temperature of the slow cooling zone is 70~80℃ and the outlet temperature is 55~65℃, and the fast cooling zone is cooled by cold air at 20~30℃.
[0033] The matte PET film of the present invention has the following beneficial effects: The PET matte film prepared by this invention has low gloss and appropriate haze, achieving an excellent low-gloss visual effect and uniform and soft light diffusion effect. The film has a large surface roughness, which can give it excellent surface adhesion, strong bonding of ink or coating, excellent printing and lamination performance, good toughness and not easy to crack. It can meet the stringent requirements of specific decorative materials, automotive decoration and other high-end fields for film appearance and durability, and can also replace downstream hot melt spray coating products. Detailed Implementation
[0034] The present invention will now be described in detail through embodiments: In the following examples and comparative examples: The mica powder has a mesh size of 3000. By mass fraction, the main components are: silicon dioxide 48%, aluminum oxide 18%, potassium oxide 10%, ferric oxide 4%, sodium oxide 1.26%, magnesium oxide 1.42%, and the remainder are other unavoidable conventional components.
[0035] The cross-linked silicone resin microspheres are model number MSE silicone microspheres from the USA.
[0036] The TPEE resin has a melt flow rate of 30 g / 10 min at 230°C and 2.16 kg, and its grade is LONGLITE®TPEE 1155LL.
[0037] The ethylene-acrylate-glycidyl methacrylate terpolymer has a melt flow rate of 6 g / 10 min at 190 °C and 2.15 kg, and its brand name is Arkema Lotader AX 8900.
[0038] The PET resin is designated Skyrol® SL30U.
[0039] The carboxylated cellulose nanofibers, with diameters of 4-10 nm and lengths of 100-500 nm, were purchased from Angxing New Carbon Materials Changzhou Co., Ltd.
[0040] The PET chips used are FG600 type PET chips supplied by Yizheng Chemical Fiber. Example 1
[0041] I. Preparation of Functional Masterbatch A: (1) Preparation of modified additives: Weigh mica powder and cross-linked organosilicon resin microspheres in a mass ratio of 1:1 and add them to a mixer. Set the mixer to 500 rpm and turn on the heating jacket to raise the material temperature to 60±5℃. Keep the temperature and stir for 15 min. Then weigh KH550 coupling agent, the amount of which is 0.8% of the total mass of mica powder and cross-linked organosilicon resin microspheres. Dissolve KH550 coupling agent in 8 times the mass of anhydrous ethanol and stir until completely dissolved to prepare a coupling agent solution. Adjust the mixer speed to 1500 rpm and lower the temperature to room temperature. Add the coupling agent solution to the mixer and continue stirring for 5 min. Then discharge the material and transfer the mixture to a vacuum oven. Dry it at 80℃ and vacuum degree -0.09MPa for 4 h. After drying to room temperature, take it out and pass it through a 100-mesh sieve to obtain the modified additives. (2) Preparation of raw materials for functional masterbatch A: By weight, prepare 20.4 parts of modifying agent, 40.5 parts of TPEE resin, 10.2 parts of ethylene-acrylate-glycidyl methacrylate terpolymer, 0.25 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (antioxidant 1010), 0.32 parts of calcium stearate, and 28.65 parts of PET resin; (3) Add the raw materials of the above functional masterbatch A into a mixer, stir at 300 rpm for 2 min at room temperature, and then stir at 1500 rpm for 5 min to obtain a mixture. (4) The mixture is melt-extruded in a twin-screw extruder (the screw speed is 120 rpm, and the temperature of each zone of the extruder is set sequentially from the feed port to the die as follows: Zone 1 210℃, Zone 2 235℃, Zone 3 255℃, Zone 4 265℃, Zone 5 265℃, Zone 6 260℃, Zone 7 250℃, and the die temperature is 240℃. A vacuum pump is connected in Zone 5 (exhaust section). After each zone reaches the set temperature, it is kept warm for 30 minutes. The vacuum pump is started to make the vacuum degree of the exhaust section reach below -0.08MPa). The strip extruded from the die is cooled fully in a water tank (water temperature 20±5℃), and then the surface moisture is dried with an air knife. It is then pelletized in a pelletizer to obtain functional masterbatch A (particle diameter is 2~3mm and length is 3~4mm).
[0042] II. Preparation of Functional Masterbatch B: Carboxylated cellulose nanocrystals and PET resin at a mass ratio of 15:100 were added to a mixer and stirred at 500 rpm for 10 minutes. The mixture was then fed into a twin-screw extruder with a screw speed of 120 rpm. The temperatures of each zone of the extruder were set as follows: Zone 1 180℃, Zone 2 190℃, Zone 3 200℃, Zone 4 210℃, Zone 5 200℃, and the die temperature 195℃. A vacuum pump was connected to Zone 3 (exhaust section). After each zone reached the set temperature, the temperature was maintained for 30 minutes. The vacuum pump was then started to bring the vacuum level of the exhaust section down to below -0.08 MPa. The extruded strips were thoroughly cooled in a water bath (water temperature 20±5℃), and then the surface moisture was dried with an air knife before being pelletized in a pelletizer to obtain functional masterbatch B (particle diameter 2~3 mm, length 3~4 mm).
[0043] III. Preparation of Matte PET Film: S1. Add PET chips (8:1.5:1), functional masterbatch A, and functional masterbatch B to a mixer and mix at 500 rpm for 30 minutes to obtain a mixture. S2. Transfer the mixture to a vacuum drum dryer, set the drying temperature to 165±2℃, turn on the vacuum pump to make the vacuum degree reach below -0.095MPa, and dry for 5 hours. During this period, turn off the vacuum and fill with nitrogen every hour, and rotate the dryer to turn the material over once to ensure uniform drying, so that the moisture content of the mixture is reduced to below 50ppm, and the dried mixture is obtained. S3. The dried mixture is added to a single-screw extruder for melt extrusion. The screw speed is 25 rpm. The heating section of the barrel is set with the following temperatures sequentially from the feed port to the die: Zone 1 240℃, Zone 2 270℃, Zone 3 285℃, Zone 4 290℃, and Zone 5 285℃. The melt in the extruder passes through two filters: the first filter has a precision of 20μm, and the second filter has a precision of 15μm. After that, the melt is discharged through a T-die. After flowing out of the T-die, the melt is cast onto a cooling roller with a surface temperature of 30±1℃. It is cooled by the roller with the assistance of an air knife and then wound up by a traction roller at a speed of 5m / min to obtain a casting sheet with a thickness of 400±5μm. S4. The cast sheet is first stretched longitudinally at 85±1℃ with a longitudinal stretching ratio of 3.4 times, and then stretched laterally at 115±1℃ with a lateral stretching ratio of 3.7 times. After stretching, it enters the heat setting zone at 235±2℃ with a hot air velocity of 5m / s for 20 seconds. Then, it is cooled to below 40℃ in the slow cooling zone (inlet temperature of 70℃ and outlet temperature of 55℃) and the fast cooling zone (30℃ cold air) before being wound up to obtain a matte PET film. Example 2
[0044] I. Preparation of Functional Masterbatch A: The method of Example 1 is followed, except that the raw materials for functional masterbatch A in step (2) are prepared as follows: by weight, 22 parts of modifying agent, 38 parts of TPEE resin, 12 parts of ethylene-acrylate-glycidyl methacrylate terpolymer, 0.3 parts of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] (antioxidant 1010), 0.3 parts of calcium stearate, and 27.4 parts of PET resin are prepared, and the rest are the same as in Example 1.
[0045] II. Preparation of Functional Masterbatch B: The procedure was carried out in accordance with the method of Example 1, except that the mass ratio of carboxylated cellulose nanocrystals to PET resin was 18:100, and the rest was the same as in Example 1.
[0046] III. Preparation of Matte PET Film: The method was carried out in accordance with Example 1, except that functional masterbatch A and functional masterbatch B of this example were used, and the mass ratio of PET chips, functional masterbatch A and functional masterbatch B was 8:1.8:1.2. The rest was the same as in Example 1. Example 3
[0047] I. Preparation of Functional Masterbatch A: The method was carried out in accordance with Example 1, except that in step (1), the mass ratio of mica powder to cross-linked silicone resin microspheres was 1.2:1, and the amount of KH550 coupling agent was 0.6% of the total mass of mica powder and cross-linked silicone resin microspheres; in step (2), the amount of TPEE resin was 40.4 parts, the amount of ethylene-acrylate-glycidyl methacrylate terpolymer was 10.3 parts, and the rest was the same as in Example 1.
[0048] II. Preparation of Functional Masterbatch B: The procedure was carried out in accordance with the method of Example 1, except that the mass ratio of carboxylated cellulose nanocrystals to PET resin was 12:100, and the rest was the same as in Example 1.
[0049] III. Preparation of Matte PET Film: The method was carried out in accordance with Example 1, except that functional masterbatch A and functional masterbatch B of this example were used, and the mass ratio of PET chips, functional masterbatch A and functional masterbatch B was 8:1.3:1.8. The rest was the same as in Example 1. Example 4
[0050] I. Preparation of Functional Masterbatch A: The method of Example 1 was followed, except that the mass ratio of mica powder to cross-linked organosilicon resin microspheres in step (1) was 0.5:1, and the rest was the same as in Example 1.
[0051] II. Preparation of Functional Masterbatch B: Same as in Example 1
[0052] III. Preparation of Matte PET Film: The method is the same as in Example 1, except that the functional masterbatch A of this example is used. Example 5
[0053] I. Preparation of Functional Masterbatch A: The method of Example 1 was followed, except that in step (2), the amount of TPEE resin was 25.5 parts and the amount of ethylene-acrylate-glycidyl methacrylate terpolymer was 25.2 parts, and the rest was the same as in Example 1.
[0054] II. Preparation of Functional Masterbatch B: Same as in Example 1
[0055] III. Preparation of Matte PET Film: The method is the same as in Example 1, except that the functional masterbatch A of this example is used. Example 6
[0056] I. Preparation of Functional Masterbatch A: Same as Example 1.
[0057] II. Preparation of Functional Masterbatch B: The procedure was carried out in accordance with the method of Example 1, except that the mass ratio of carboxylated cellulose nanocrystals to PET resin was 5:100, and the rest was the same as in Example 1.
[0058] III. Preparation of Matte PET Film: The method of Example 1 was followed, except that functional masterbatch B of this example was used, and the mass ratio of PET chips, functional masterbatch A and functional masterbatch B was 8:1.5:0.4. The rest was the same as in Example 1.
[0059] Comparative Example 1 I. Preparation of Functional Masterbatch A: The procedure was carried out in accordance with the method of Example 1, except that the mica powder and cross-linked silicone resin microspheres in a mass ratio of 1:1 were replaced with an equal mass of mica powder, and the rest was the same as in Example 1.
[0060] II. Preparation of Functional Masterbatch B: Example
[0061] III. Preparation of Matte PET Film: The method is the same as in Example 1, except that the functional masterbatch A of this example is used.
[0062] Comparative Example 2 I. Preparation of Functional Masterbatch A: The procedure was carried out in accordance with the method of Example 1, except that the mica powder and cross-linked silicone resin microspheres in a mass ratio of 1:1 were replaced with cross-linked silicone resin microspheres of equal mass, and the rest was the same as in Example 1.
[0063] II. Preparation of Functional Masterbatch B: Example
[0064] III. Preparation of Matte PET Film: The method is the same as in Example 1, except that the functional masterbatch A of this example is used.
[0065] Comparative Example 3 I. Preparation of Functional Masterbatch A: The method of Example 1 was followed, except that no modifying agent was added during the preparation of functional masterbatch A, and the other raw materials for functional masterbatch A were prepared in the same proportion, and the rest was the same as in Example 1.
[0066] II. Preparation of Functional Masterbatch B: Same as in Example 1
[0067] III. Preparation of Matte PET Film: The method is the same as in Example 1, except that the functional masterbatch A of this example is used.
[0068] Comparative Example 4 The method of Example 1 was followed, except that TPEE resin and ethylene-acrylate-glycidyl methacrylate terpolymer were not added during the preparation of functional masterbatch A. The other raw materials for functional masterbatch A were prepared in the same proportion, and the rest was the same as in Example 1.
[0069] II. Preparation of Functional Masterbatch B: Same as in Example 1
[0070] III. Preparation of Matte PET Film: The method is the same as in Example 1, except that the functional masterbatch A of this example is used.
[0071] Comparative Example 5 The procedure was carried out according to Example 1, except that functional masterbatch B was not prepared and used; only PET chips and functional masterbatch A were used in a mass ratio of 8:1.5. The rest was the same as in Example 1.
[0072] Comparative Example 6 I. Preparation of Functional Masterbatch A: Same as Example 1.
[0073] II. Preparation of Functional Masterbatch B: The procedure was carried out in accordance with the method of Example 1, except that the mass ratio of carboxylated cellulose nanocrystals to PET resin was 30:100, and the rest was the same as in Example 1.
[0074] III. Preparation of Matte PET Film: The method of Example 1 was followed, except that functional masterbatch B of this example was used, and the mass ratio of PET chips, functional masterbatch A and functional masterbatch B was 8:1.3:2. The rest was the same as in Example 1.
[0075] Performance testing The following performance tests were performed on the PET matte films in the examples and comparative examples.
[0076] 1. Gloss test: The test shall be conducted in accordance with ASTM-D2457-2008.
[0077] 2. Haze test: A haze meter is used for testing.
[0078] 3. Surface roughness Ra test: Tested by white light interference 3D profile.
[0079] 4. Elongation at break: Tested according to ASTM D-882 standard.
[0080] 5. Evaluation of surface stickiness: At room temperature (23±2℃), laboratory personnel gently press the film surface with the pad of a dry, clean index finger and slide it laterally for about 2-3cm. Based on the feel, it is divided into 4 levels: Level 0 is completely dry, and the sliding is smooth without any stickiness; Level 1 is slightly sticky, and there is slight damping but no dragging when sliding; Level 2 is obviously sticky, and the finger feels like it is being sucked in, and the sliding resistance is obvious; Level 3 is severely sticky, and the finger is difficult to slide, and the film surface may even be lifted with the finger, and a peeling sound can be heard.
[0081] The test results are shown in Table 1.
[0082] Table 1 Performance Test Results
[0083] The test results above show that the PET matte film of this invention has the advantages of low gloss, high diffusion, high adhesion, high toughness, and strong printing and lamination.
Claims
1. A low-gloss PET matte film, characterized in that, The matte PET film is made from raw materials comprising the following components: PET chips, functional masterbatch A, and functional masterbatch B; wherein functional masterbatch A includes modifying agents, thermoplastic polyester elastomer, and olefin copolymer containing epoxy functional groups. The functional masterbatch B contains carboxylated cellulose nanocrystals and PET resin; the modifying agent is a composite microparticle surface-treated with a silane coupling agent, and the composite microparticle is composed of layered silicate and cross-linked organosilicon resin microspheres.
2. The low-gloss PET matte film according to claim 1, characterized in that, The layered silicate is mica powder; the mass ratio of layered silicate to cross-linked organosilicon resin microspheres in the composite microparticles is (0.5~2):1; the silane coupling agent is γ-aminopropyltriethoxysilane.
3. The low-gloss PET matte film according to claim 1, characterized in that, The thermoplastic polyester elastomer is TPEE resin; the olefin copolymer containing epoxy functional groups is an ethylene-acrylate-glycidyl methacrylate terpolymer.
4. The low-gloss PET matte film according to claim 1, characterized in that, The weight ratio of the modified additive, thermoplastic polyester elastomer, and epoxy-functionalized olefin copolymer is (15~25):(35~45):(8~15).
5. The low-gloss PET matte film according to claim 3 or 4, characterized in that, By weight, the functional masterbatch A comprises: 15-25 parts of modifying agent, 35-45 parts of thermoplastic polyester elastomer, 8-15 parts of olefin copolymer containing epoxy functional groups, 0.1-0.5 parts of antioxidant, 0.1-0.5 parts of dispersant, and 20-30 parts of PET resin.
6. The low-gloss PET matte film according to claim 1, characterized in that, The carboxylated cellulose nanocrystals have a diameter of 2-15 nm and a length of 100-300 nm; the mass ratio of carboxylated cellulose nanocrystals to PET resin in the functional masterbatch B is (10-20):
100.
7. The low-gloss PET matte film according to claim 1, characterized in that, The mass ratio of the PET chips, functional masterbatch A and functional masterbatch B is (7~9):(1~2.5):(1~2).
8. A process for preparing a low-gloss PET matte film according to any one of claims 1 to 7, characterized in that, Includes the following steps: PET chips, functional masterbatch A and functional masterbatch B are mixed evenly in proportion and dried until the moisture content is ≤50ppm. The dried mixture is melt-extruded through a single screw extruder and cast onto a cooling roller through a T-die to obtain a cast sheet. The cast sheet is biaxially stretched, heat-set after stretching, cooled and wound up to obtain a low-gloss PET matte film.
9. The preparation process of the low-gloss PET matte film according to claim 8, characterized in that, The barrel temperature of the single-screw extruder from the feed port to the die head is as follows: Zone 1 230~250℃, Zone 2 260~280℃, Zone 3 280~290℃, Zone 4 285~295℃, Zone 5 280~290℃, and the die head temperature is 270~280℃; the surface temperature of the cooling roller is 25~35℃.
10. The preparation process of the low-gloss PET matte film according to claim 8, characterized in that, The biaxial stretching adopts a step-by-step stretching method, first longitudinal and then transverse. The longitudinal stretching temperature is 80~90℃ and the stretching ratio is 3.2~3.6 times; the transverse stretching temperature is 110~130℃ and the stretching ratio is 3.5~4 times.
